Diction and Message Logic in the Podcast of Deddy Corbuzier in Episode "Malih, Pesan Pedas Tuk Ade Londok" - Ronald Umbas; I Gusti Agung Sri Rwa Jayantini (RETORIKA: Jurnal Ilmu Bahasa, 2021)
This study aims to identify diction which is related to message logic in communicating on social media. The identification is carried out based on Deddy Corbuzierâ€™s podcast that is aired on YouTube. The analysis of diction is an interesting study when, as one of the reasons, it is related to the efforts to effectively convey messages that are beneficial to a society. This study combines the concept of diction and Message Logic Theory, particularly "message design logic." The method applied is observation on the data source in the form of a video recording with note-taking techniques by which identification, classification and data reduction could be carried out. There are two main results in this study. First, the diction includes general words consisting of graded words and abstract words, and particular words consisting of proper names and the words that have suggestive power. Second, the dominant message logic that appears in Deddy Corbuzier's podcast episode "Malih, Pesan Pedas Tuk Ade Londokâ€ (Malih, Sharp Message for Ade Londok) is expressive logic and rhetorical logic. The implication of this research on diction and communication logic is a description of the importance of choosing the right words in public spaces. This study also recommends other researchers to do further researches by using more speech data so that public communication patterns can be mapped better.